Physicochemical Properties of Gold Nanostructures Deposited on Glass. (2nd June 2014) - Novotna, Zdenka; Reznickova, Alena; Viererblova, Linda; Kolafa, Jiri; Kolska, Zdenka; Riha, Jan; Svorcik, Vaclav
Abstract : Properties of gold films sputtered onto borosilicate glass substrate were studied. UV-Vis absorption spectra were used to investigate optical parameters. XRD analysis provided information about the gold crystalline nanostructure, the texture, and lattice parameter and biaxial tension was also determined by the XRD method. The surface morphology was examined by atomic force microscopy (AFM); chemical structure of sputtered gold nanostructures was examined by X-ray photoelectron spectroscopy (ARXPS). The gold crystallites are preferentially [111] oriented on the sputtered samples. Gold deposition leads to dramatic changes in the surface morphology in comparison to pristine glass substrate. Oxygen is not incorporated into the gold layer during gold deposition. Experimental data on lattice parameter were also confirmed by theoretical investigations of nanoclusters using tight-binding potentials.